2021
DOI: 10.1051/e3sconf/202123103003
|View full text |Cite
|
Sign up to set email alerts
|

Line Width Mathematical Model in Fused Deposition Modelling for Precision Manufacturing

Abstract: Additive manufacturing is becoming increasingly popular because of its unique advantages, especially fused deposition modelling (FDM) which has been widely used due to its simplicity and comparatively low price. However, in current FDM processes, it is difficult to fabricate parts with highly accurate dimensions. One of the reasons is due to the slicing process of 3D models. Current slicing software divides the parts into layers and then lines (paths) based on a fixed value. However, in a real printing process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Previous studies have demonstrated that enlarging the line width decreases gaps and defects between adjacent lines and layers. These findings align with the existing literature 36–38 …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have demonstrated that enlarging the line width decreases gaps and defects between adjacent lines and layers. These findings align with the existing literature 36–38 …”
Section: Resultssupporting
confidence: 92%
“…These findings align with the existing literature. [36][37][38] One significant drawback of 3D printing is the long production time. 25,39 The nozzle diameter, printing speed, line width, and layer height are the most critical parameters influencing production time.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, heating of the previous layer leads to welding of the beads. During the welding process, a short-term partial melting of the surface of the previous layer may occur [3,12,24,25].During the printing process, the extruded bead is pressed against the previous layer by the nozzle and is deformed, exerting pressure on the adjoining bead, and contributing by that to the formation of a weld [25][26][27][28][29].…”
Section: The Mechanism Of Materials Formation By Welding Of Thermopla...mentioning
confidence: 99%
“…Nowadays, the latest versions of slicer software have recommended parameter settings depending on the model. A formula was derived to compute the line width at different layer heights [4]. This theoretical method can be used to calculate the optimum line width for 3D printed parts however, an experimental investigation is needed to assess the accuracy of this method [4].…”
Section: Introductionmentioning
confidence: 99%
“…A formula was derived to compute the line width at different layer heights [4]. This theoretical method can be used to calculate the optimum line width for 3D printed parts however, an experimental investigation is needed to assess the accuracy of this method [4]. An experimental study on the compressive strength of a 3D model using five parameter settings was studied and it was concluded that a layer thickness of 0.254 mm, orientation of 0.036 o , raster angle of 59.44 o , raster width of 0.422 mm, and air gap of 0.00026 mm will yield a compressive stress of 17.4751 MPa [5].…”
Section: Introductionmentioning
confidence: 99%